Synthesis, Characterization, Biological Evaluation, DFT Studies and Molecular Docking of Novel 12-(2-(1H-Imidazol-1-yl)quinolin-3-yl)-8-methyl-2,3,4,12-tetrahydro- 1H-benzo[4,5]thiazolo[2,3-b]quinazolin-1-one and its Derivatives - Sharma, Puja; Patel, Rajat; Koshti, Rohit R.; Vyas, Akshay; Sangani, Chetan B. (Asian Journal of Chemistry, 2023)
Twelve new compounds were synthesized consisting of biquinoline-imidazole-benzothiazole hybrids 6a-l using a base catalyzed one pot MCR reaction, these were then screened for in vitro biological activities against cancer cell lines. Among the twelve prepared potential anticancer agents, compound 6j was found to be the most active against EGFR (IC50 of 0.14 ± 0.03 Μm), A549 and HepG2, also the same derivative of the series was found to be most active against FabH (IC50 of 3.1 Μm) E. coli. Further the molecules were analysed for DFT and molecular docking studies to calculate the distance and angle between the active parts of the molecules as well as charge density distribution over the molecules which provides a qualitative measure for the effective the binding of molecules in the active pockets with greater binding affinity.